Thirteen-year-old Child Develops Squamous Cell Carcinoma Without Underlying Causes - Ali Kuru, MD; Omer Kokacya, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Histologically, only 1%–2% of excised skin tumors are malignant. Cutaneous squamous cell carcinoma is rare in children. Several cases have been reported in the literature. In most cases, there are underlying predispositions in children, such as xeroderma pigmentosum, albinism, and immunosuppression. Presently, the patient did not have any underlying medical conditions or a family history of cutaneous squamous cell carcinoma.